KOMITMEN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KOPPERINDAG DAN UMKM KABUPATEN DHARMASRAYA - elsy Oktavia; Syamsul Amar (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The purpose of this study was to analyze: 1) the effect of leadership on organizational culture, 2) the effect of leadership on employee commitment, 3) the influence of organizational culture on employee commitment, 4) The effect of leadership on employee performance, 5) The influence of organizational culture on employee performance , 6) Effect of work commitment on employee performance. The population of this study were all employees of the Dinas Kopperindag dan UMKM Kabupaten Dharmasraya totaling 63 people. The sampling method is proportional stratified random sampling. The number of samples is 54 employees. Data analysis techniques to test the hypothesis of the study was the analysis of line with kaedah kaedah test used was the F test and t test. The results of the study found that: 1) Leadership significant positive impact on organizational culture and Dinas Kopperindag dan UMKM Kabupaten Dharmasraya. 2) Leadership significant positive impact on employee commitment Dinas Kopperindag dan UMKM Kabupaten Dharmasraya. 3) Organizational culture have a significant positive impact on employee commitment Dinas Kopperindag dan UMKM Kabupaten Dharmasraya. 4) Leadership significant positive effect on the performance of Dinas Kopperindag dan UMKM Kabupaten Dharmasraya. 5) organizational culture have a significant positive effect on employee performance Dinas Kopperindag dan UMKM Kabupaten Dharmasraya. 6) Commitment work significantly positive effect on employee performance Dinas Kopperindag dan UMKM Kabupaten Dharmasraya. In an effort to improve the performance of employees in the Dinas Kopperindag dan UMKM Kabupaten Dharmasraya need to be improved implementation of leadership functions, improve organizational culture and improving work commitment in carrying out duties